Teachers’ Strategies Using Canva for Recount Writing in EFL Classrooms - Dea Aviani; Wahyu Taufiq (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital technologies have become integral to contemporary language education, particularly in supporting multimodal learning in English as a Foreign Language (EFL) contexts. Specific Background: Writing, especially recount text composition, remains a complex skill for EFL learners due to demands on organization, grammar, and creativity, prompting teachers to adopt visual–digital tools such as Canva to support instruction. Knowledge Gap: Despite growing use of Canva in classrooms, limited research has examined how teachers strategically design, implement, and adapt Canva-based writing lessons in authentic EFL settings. Aims: This study aimed to explore teachers’ strategies in using Canva to support students’ recount text writing in an Indonesian junior high school. Results: Using a qualitative case study involving two English teachers, data from interviews, observations, and document analysis revealed three core strategies: purposeful planning aligned with genre structure, visual scaffolding during writing activities, and adaptive responses to technological and learner challenges. Novelty: The study provides an in-depth description of pedagogically grounded practices showing Canva as a structured instructional tool rather than merely a design application. Implications: Findings suggest that successful integration of visual-digital platforms in EFL writing depends on teacher readiness, digital competence, and flexible instructional design, offering practical guidance for educators seeking to implement technology-supported writing instruction. Highlights: Instructional planning aligned visual templates with narrative structure components. Guided frameworks enabled learners to organize ideas while composing texts. Flexible adjustments addressed connectivity issues and varying technical abilities. Keywords: Canva; EFL Writing; Recount Text; Teacher Strategies; Digital Pedagogy